Games, Learning, and Society : Learning and Meaning in the Digital Age - Steinkuehler, Constance; Squire, Kurt; Barab, Sasha (Cambridge : Cambridge University Press, 2012)
This volume is the first reader on video games and learning of its kind. Covering game design, game culture and games as twenty-first-century pedagogy, it demonstrates the depth and breadth of scholarship on games and learning to date. The chapters represent some of the most influential thinkers, designers and writers in the emerging field of games and learning - including James Paul Gee, Soren Johnson, Eric Klopfer, Colleen Macklin, Thomas Malaby, Bonnie Nardi, David Sirlin and others. Together, their work functions both as an excellent introduction to the field of games and learning and as a powerful argument for the use of games in formal and informal learning environments in a digital age.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).
Keywords: Learning, Psychology of